1999
DOI: 10.1046/j.1365-3059.1999.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to stem canker (Phomopsis helianthi) in sunflower

Abstract: Six male sterile sunflower lines were crossed with seven restorers in a factorial mating design. The 13 inbred lines and their 42 F1 hybrids were planted in a randomized block design with three replicates. Each replicate consisted of two rows, 5 m long (30–35 plants per replicate). Resistance to natural Phomopsis infection, presented as the percentage of plants with no encircling necrosis lesions of the fungus on the main stem, was determined at physiological maturity. Analysis of variance showed that female a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Use of natural infection for screening germplasm to PSC has been reported previously (Degléne et al, 1999). Another method of inoculation is the seminatural method of Viguié et al (2000), who reported a success rate of 50% in obtaining sufficiently homogeneous levels of PSC attack.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of natural infection for screening germplasm to PSC has been reported previously (Degléne et al, 1999). Another method of inoculation is the seminatural method of Viguié et al (2000), who reported a success rate of 50% in obtaining sufficiently homogeneous levels of PSC attack.…”
Section: Resultsmentioning
confidence: 99%
“…Soon after its discovery, PSC had rapidly become a serious disease of sunflower in European countries and frequently caused economic damage, with yield loss as high as 40% (Mihaljcevic et al, 1982;Acimovic, 1984;Škoric´, 1985;Masirevic and Gulya, 1992;Debaeke et al, 2003). Further studies have suggested that Phomopsis resistance is quantitative in nature and governed by mostly additive gene action (Vear et al, 1997;Degener et al, 1999;Degléne et al, 1999;Viguié et al, 1999;Viguié et al, 2000;Langar et al, 2004). Phomopsis stem canker is becoming wider in global distribution, as recent reports suggest significant damage to sunflower crops in parts of Australia, especially in areas with extended wet periods (Thompson et al, 2011).…”
mentioning
confidence: 99%
“…Similarly, heterosis might be an important factor explaining the bruising resistance of hybrids between the most bruising resistant homokaryon Mes09143 and the most bruising sensitive homokaryon Z8. The difference between the observed performance of an F1 hybrid and the expected value based on the GCA of its parents indicate gene interactions [8]. The better than expected performance of the hybrid between Mes09143 and Z8 cannot be explained by additive effects alone but indicate interference between alleles (dominance or even over-dominance).…”
Section: Discussionmentioning
confidence: 99%
“…The GCA of inbred lines is determined and used in maize breeding to predict promising hybrids [6,7]. This approach was also successfully applied in the development of sunflower hybrids with improved resistance to Phomopsis [8]. Interesting combining ability analyses were recently performed in watermelon [9] and oil palm [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation